2018
DOI: 10.1111/jocn.14554
|View full text |Cite
|
Sign up to set email alerts
|

Nursing home resident relationship types: What supports close relationships with peers & staff?

Abstract: Nurses can be intentional about resident placements in the facility to promote social interactions and keep social goals in mind when making medical or staffing decisions to prevent interruption of important relationships.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 38 publications
2
27
0
Order By: Relevance
“…Indeed, spending ‘non-care’ time together is crucial for residents to develop close friendships with staff. 25 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, spending ‘non-care’ time together is crucial for residents to develop close friendships with staff. 25 …”
Section: Discussionmentioning
confidence: 99%
“… 23 These findings are significant given the central importance of relationships in the lives of residents. 13 , 24 , 25 However, none of these studies focused specifically on social relationships or social wellbeing, and most considered only one art-form. In contrast, the study reported here explored the impact of participatory arts across different art-forms on the social relationships between older people, and between older people and care home staff, within Essex care homes.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these important insights from early studies of the social lives of NH residents and a growing body of literature highlighting the importance of person‐ and relationship‐centred care, few studies examine relationships from the perspective of residents themselves. Recent empirical studies on social relationships in NHs have been conducted primarily using researcher‐ or staff‐administered structured surveys or open‐ended interviews that examined staff perspectives without including resident perspectives (Roberts, ; Roberts & Bowers, ). In addition, few studies have focused on the broader social network of residents beyond the caregiver and care recipient relationships.…”
Section: Introductionmentioning
confidence: 99%
“…Above all, NH staff have reported implementing multiple strategies based on a deep knowledge of their residents and their interactions: this seems to confirm the need to ensure both the stability of the dyad (carer and resident) [ 42 ] but also the stability of the entire staff to maximise this knowledge and the consequent decisions. This contrasts the tendency of some NHs to recruit temporary or informal staff [ 43 ].…”
Section: Discussionmentioning
confidence: 89%